(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Distance education as we know it today began with whatMoore called the third generation of Distance Education. The period was the2000s and early 2000s. Moore stated that this was a time of critical change indistance education, resulting from several experiments with new ways oforganizing technology and human resources, leading to new instructionaltechniques and new educational theorizing. (Moore and Kearsley, 2005) Astechnology progressed, so did the progression of distance education. By the2000’s, it had achieved broad acceptance and in the 2000s, it “arrived” as oneof the “flavors of the decade” in education, in higher education especially.(Moore and Anderson, 2003). Garrison and Shale (2007) recognized the move intoan Information Age characterized by technologies capable of interactive andindividualized education at a distance in 2007.